Due Obedience for Illegitimate Orders: a Case Study of Embezzlement in Ecuador and Colombia - Ponce Andrade, Ana Lucía; Villagómez Cabezas, Richard; Piedrahita Bustamante, Pedro (Revista del CLAD Reforma y Democracia, 2022)
This paper analyzes due obedience in the crime of embezzlement in two cases of Ecuadorian and Colombian jurisprudence, from the perspective of criminal law, public administration and social psychology. The qualitative approach and the multiple case study technique with three propositions are used. It is shown that the superior’s deviation when issuing an order entails an ethical and legal dilemma for the subordinate official, who must analyze the content of the order because his decision has criminal consequences that lead to embezzlement. It is concluded that the lack of questioning of the officials against the orders received from their superiors configures the presumption of legality in such orders or the implementation of a common criminal objective between the superior and the subordinate.